2020
DOI: 10.3390/antibiotics9100646
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Multidrug Resistance of Helicobacter pylori and Its Impact on Eradication in Korea from 2017 to 2019: A Single-Center Study

Abstract: Antimicrobial resistance is one of the major factors determining the efficacy of Helicobacter pylori eradication therapy. This study aimed to estimate the recent prevalence of multidrug resistance of H. pylori and its impact on eradication in Korea. A total of 174 patients were prospectively enrolled at Chung-Ang University Hospital from 2017 to 2019. H. pylori strains were isolated from the gastric body and antrum. The minimum inhibitory concentrations of antibiotics were determined by the serial twofold agar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
3
22
0
2
Order By: Relevance
“…18 A moderate resistance rate was detected in France (58.6%) 23 and Korea (27%). 24 The high resistance rates may be due to the widespread use of metronidazole for other infectious diseases, such as parasitic intestinal infections and genital infections. Metronidazole is cheap and overused and is an over-the-counter drug in developing countries such as Egypt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 A moderate resistance rate was detected in France (58.6%) 23 and Korea (27%). 24 The high resistance rates may be due to the widespread use of metronidazole for other infectious diseases, such as parasitic intestinal infections and genital infections. Metronidazole is cheap and overused and is an over-the-counter drug in developing countries such as Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…A very low rate of resistance was reported in France (0% using PCR) 23 and China (1.6% using E-test). 26 Slightly higher resistance rates were detected in China 18 (7.7% using the disk diffusion or E-test), Palestine (18%), 22 Egypt (18.3% using PCR), 27 Korea (20%), 24 and Iran (30% using the E-test). 28 The different amoxicillin resistance rates may be due to the different geographical areas or the different methods of testing resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of lansoprazole, bismuth, levofloxacin, and amoxicillin therapy compared to bismuth metronidazole tetracycline (BMT) quadruple therapy for second-line treatment of H. pylori. Studies found that sequential and hybrid therapies have found to be better eradication rate 24 , 25 in their studies showed triple and quadruple regimens patients with no compliance 2,25, In study done in Korea 18 , antibiotic resistance to clarithromycin has been reported 15%. Resistance against both clarithromycin and metronidazole reported was 8.6%.…”
Section: Discussionmentioning
confidence: 98%
“…It is very important to have a good understanding of regional antibiotic resistance patterns of H. pylori for the implementation of effective empirical eradication therapies and adequate rescue therapies. The study conducted by Park and coworkers investigated the antibiotic resistance patterns of H. pylori and their impact on eradication in Seoul in recent years [ 13 ]. Their results suggested alarming data: the rate of multidrug resistance is increasing, and standard triple therapy (STT) is no longer an acceptable first-line option for H. pylori eradication in Korea.…”
mentioning
confidence: 99%